Contribution to an efficient transmission of information to the textile fashion consumer and the influence in sustainable attitudes - Carneiro, Noémia (2016)
The concepts involved in sustainable textile fashion, demanding good knowledge about raw materials, processes, end use properties and circuits amongst others, are able to determine the way the textile product is designed and the behavior of the consumer, regarding life style and buying decisions. The textile product`s life integrates raw materials, their processing, distribution, use by the consumer and destination of the product after useful lifetime, this is, his complete life cycle. It is very important to recognize the power of the consumer to influence parameters related to sustainability, namely when he decides how, when and why he buys and afterwards by the attitudes taken during and after use. The conscious act of consumption involves ethical, ecological and technical knowledge in which the concern is overall lifecycle of the fashion product and not exclusively aesthetic and symbolic values strongly related with its ephemeral nature. The present work proposes the classification of textile products by means of an innovative label aiming to establish a rating related to the Life of Fashion Products, by using parameters considered with especial impact in lifecycle, as textile fibers, processing conditions, generated wastes, commercialization circuits, durability and cleaning procedures. This label for sustainable fashion products aims to assist the stakeholders with informed attitudes and correct decisions in order to promote the objectives of sustainable fashion near designers, consumers and industrial experts.